PENERAPAN MODEL BRAIN WRITING UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN NARASI SISWA SEKOLAH DASAR - Adelina, Sisilia Deli; Surya, Yenni Fitria; Fadhilaturrahmi, Fadhilaturrahmi (Jurnal Muassis Pendidikan Dasar, 2023)
This study aims to determine the improvement of narrative writing skills by applying the Brain Writing model to the fifth grade students of SDN 012 Langgini. This type of research is classroom action research (CAR) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation, and reflection. Data collection techniques are documentation, tests and observations. The results of this study can be concluded that in the skills of writing narrative essays for class V SDN 012 Langgini in the first cycle of the first meeting, there were 8 students with a percentage of 47.05%. Furthermore, in the first cycle of the second meeting of the students who completed there were 9 students with a percentage of 52.94%. While in the second cycle of the first meeting, 11 students completed the first meeting with a percentage of 64.70%. Finally, in the second cycle of the second meeting, there were 14 students who completed the second meeting with a percentage of 82.35%. Thus, it can be concluded that the application of the Brain Writing model can improve the skills of writing narrative essays in the fifth grade of SDN 012 Langgini.